Comparison of diabetes knowledge and self-efficacy in diabetes management among the urban people and the people from Garo tribe in Mymensingh division - Hossain, Md. Rafayat (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.